Qualitative evaluation of the Rey-Osterrieth Complex Figure Test in patients with progressive supranuclear palsy - Tommasini, L.; Bonaccorsi, J.; Del Prete, E.; Cintoli, S.; Pagni, C.; Mazzucchi, S.; Palermo, G.; Morganti, R.; Frosini, D.; Siciliano, G.; Tognoni, G.; Ceravolo, R. (Clinical neuropsychologist, 2023)
Objective: In early stages of disease, the differential diagnosis between Parkinson's Disease (PD) and atypical parkinsonism, such as Progressive Supranuclear Palsy (PSP), could be challenging. Growing attention has recently been dedicated to investigating neuropsychological markers of degenerative parkinsonism. The Rey-Osterrieth Complex Figure Test (ROCFT) copy score was hypothesized able to differentiate PSP from PD. However, ROCFT is a drawing test requiring multiple cognitive abilities and it is still unknown which of them assumes an important role in PSP performance. Using a qualitative scoring system, we investigated which cognitive abilities underpin the PSP performance at the ROCFT copy trial. Moreover, we evaluated usefulness of the BQSS scores in discriminating PSP from PD. Methods: Thirty PSP-Richardson's Syndrome (PSP-RS) patients, 30 PD patients, and 30 healthy control (HC) comparable for age, education, and gender were enrolled. All subjects underwent a neuropsychological evaluation; ROCFT copy were evaluated with the 36-Point Score and with the Boston Qualitative Scoring System (BQSS). Results: PSP-RS patients performed worse in ROCFT 36-Point Score and in several BQSS scores compared to other groups. Most suitable scores discriminating PSP-RS from PD were "Perseveration" and "Vertical Expansion" of BQSS. A logistic regression model considering "Perseveration" and "Vertical Expansion" showed a diagnostic accuracy of 83,3% for PSP-RS condition. Conclusion: our findings showed that "Perseveration" and "Vertical Expansion" BQSS scores were useful in discriminating PSP-RS from PD. "Perseveration" and "Vertical Expansion" BQSS scores might be included in the cognitive evaluation along with quantitative scores when PSP diagnosis is considered.